Retinoic acid enhances growth of human early erythroid progenitor cells in vitro. - Douer, D (1982)
We studied the effect of retinoic acid on the clonal proliferation of normal human early erythroid progenitor cells in vitro. Normal peripheral blood cells were cultured in methylcellulose with erythropoietin and the number of burst-forming units-erythroid (BFU-E) colonies were scored on day 12 of culture. All-trans retinoic acid increased the number of colonies in a dose-response fashion. Maximal stimulation occurred at 30 nM retinoic acid, which increased the number of BFU-E by a mean of 225 +/- 25% (+/- SE) over plates containing erythropoietin alone. Colony formation increased even in the presence of maximally stimulating concentrations of erythropoietin. The 13-cis retinoic acid stimulated BFU-E proliferation in a parallel manner as the trans analogue, while retinol (vitamin A) did not affect clonal growth. This data supports further the thesis that retinoic acid, in addition to its known effect on epithelial cells, may be involved in the growth of normal hematopoietic cells.